Double Emulsion using premix membrane emulsification - Qaffaf, Aseel Hatem; Qassrawi, Hiba Ali; Bsharat, Raya Mohammad; Mohammad Khderat, Wisal (My University, 2014)
An emulsion is a mixture of two immiscible phases of which one (i .e. oil) is dispersed in another (i.e. water) which is stabilized by a surfactant. A double emulsion is simply defined as an emulsion in an emulsion. For instance water in oil emulsion is emulsified in external water phase to form water/oil/water double emulsion. Double emulsions find wide range of applications in food, cosmetic and pharmaceutical industry for encapsulation of functional ingredients such as drugs and flavors. Emulsions are commonly prepared using conventional emulsification methods such as high pressure homogenizers. However, these methods are not suitable for preparing double emulsions as the inner phase is destroyed by applied shear. In the present study, the double emulsion will be prepared using a relatively new method called premix membrane emulsification, in which a coarse premix double emulsion (w/o/w) with large droplets and wide droplet size distribution is initially prepared with gentle stirring then it is pushed through a micro porous membrane. Here the droplets are broken up into smaller droplets resulting in an emulsion with small and uniform droplets size. Result showed the premix membrane emulsification can be successfully employed for preparation of double emulsions; in which (w/o/w) emulsion with very small size (< 1µm) were obtained which is up to our knowledge the smallest size obtained so far in the literature. The effect of the of trans membrane flux and the composition of the external aqueous phase was investigated through addition of different sugars (i.e. fructose and glucose) at different concentration. Emulsions prepared with fructose as a stabilizer in the external outer phase were smaller in size and more stable than those prepared with glucose. The effect of the different parameters were expressed using one dimensionless number (Reynolds number) and the result showed the size of the droplets increases with increasing Reynolds number. To investigate the effect of using premix membrane emulsification method some experiments were done, the effect of trans-membrane pressure was the first one and the result show the droplets size were increases with increase the trans-membrane pressure (see figure 1). Effect of changing concentration and type of sugar in the outer phase was studied also The results show that the droplet size increases with increasing the concentration for both types of sugars (glucose and fructose) (see figure 2). Figure (1): The droplets’ sizes at different trans-membrane pressure Figure (2): The droplets’ sizes at different sugar types and concentrations The change of emulsifier concentration in inner phase was studied to show the effect of this changed on the size of particles ,the result show The results show that the droplet size increases with increasing span percentages( see figure 3). Figure (3): Droplets size as a function of span percentage We further investigated the effect of flow velocity inside the porous media on the final droplet size and uniformly using the Reynolds number that characterizes the flow inside the porous media. We here show five series of experiments, two in which the continuous phase concentration varied between glucose and fructose, two in which different pressures were used for fructose and glucose and one in which different span percentage were used. The final droplet to pore size ratio obtained after the final pass of each experiment is plotted against the respective Reynolds number ( see figure (4)). Figure (4): Dimensionless droplet and pore size ratio as a function of Reynolds number.